2013
DOI: 10.1007/s12519-013-0416-2
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline related injuries in children: risk factors and radiographic findings

Abstract: Children younger than 5 years old are at risk for specific proximal tibia fractures ("Trampoline Fracture"). A child jumping simultaneously with other children has a higher risk of suffering from a fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…However, there are often multiple jumpers, a practice associated with increased risk for injury on trampolines. 4,8,12,15,23,24 To our knowledge, there have been no published studies focusing on injuries at trampoline parks. This study investigates national trends in trampoline park injuries (TPIs) and compares demographic features and injury characteristics between TPIs and home trampoline injuries (HTIs).…”
mentioning
confidence: 99%
“…However, there are often multiple jumpers, a practice associated with increased risk for injury on trampolines. 4,8,12,15,23,24 To our knowledge, there have been no published studies focusing on injuries at trampoline parks. This study investigates national trends in trampoline park injuries (TPIs) and compares demographic features and injury characteristics between TPIs and home trampoline injuries (HTIs).…”
mentioning
confidence: 99%
“…Other studies revealed a preponderance of upper extremity injuries [5, 6, 10]. Klimek et al [5] for example described as the most common injuries upper extremity fractures such as supracondylar humeral and forearm fractures, which were frequently caused by a direct impact on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in a study of Klimek et al [5] repeat radiographs after 7–10 days are recommended in children with persistent complaints as an alternative to MRI. Stranzinger et al [4] described buckle/torus or transverse hairline fractures of the proximal tibial metaphysis as the most common manifestations of the “trampoline fracture”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of trampolines is increasing, along with the incidence of injuries associated with their use 9 10. One study showed that 74% of injuries occurred when more than one person was on the trampoline 11.…”
Section: Discussionmentioning
confidence: 99%